Stress induced anisotropy in Co-rich magnetic nanocomposites for inductive applications. Issue 20 (4th October 2016) - Leary, A.; Keylin, V.; Devaraj, A.; DeGeorge, V.; Ohodnicki, P.; McHenry, M.E.
Abstract: Abstract : Magnetic nanocomposites, annealed under stress, are investigated for application in inductive devices. Stress annealed Co-based metal/amorphous nanocomposites (MANCs) previously demonstrated induced magnetic anisotropies greater than an order of magnitude larger than field annealed Co-based MANCs and response to applied stress twice that of Fe-based MANCs. Transverse magnetic anisotropies and switching by rotational processes impact anomalous eddy current losses at high frequencies. Here we review induced anisotropies in soft magnetic materials and show new Co-based MANCs having seven times the response to stress annealing as compared to Fe-based MANC systems. This response correlates with the alloying of early transition metal elements (TE) that affect both induced anisotropies and resistivities. At optimal alloy compositions, these alloys exhibit a nearly linear B – H loop, with tunable permeabilities. The electrical resistivity is not a function of processing stress but trends in electrical resistivity and induced anisotropy with choice and concentration of TE content are clearly resolved. Previously reported and record-level induced anisotropies, K u, ∼20 kJ/m 3 (anisotropy fields, H K ∼ 500 Oe), in stress annealed Co-rich MANCs are increased to K u ∼ 70 kJ/m 3 ( H K > 1800 Oe) in new systems.